Surgical treatment of breast cancer in elderly; Is current evidence strong enough to implement less aggressive treatment modalities? [Ileri yaş meme kanserinde cerrahi tedavi yaklaşimi; Standart dişi tedavi uygulamalari için kanitlar ne kadar güçlüdür?] - (:unkn) unknown (Turkish Surgical Society, 2009)
Breast cancer incidence is increased in elderly women. Since these patients were mostly excluded in prospective randomized studies, no firm recommendations currently exist for the management of breast cancer in elderly. It is highly probable that older women have one or more significant co-morbid diseases and moreover, their functional capacity is independently reduced. Also, previous studies provided that biological features of breast cancer are favourable in older women. Observational reports showed that older women with breast cancer are currently undertreated when compared to their younger counterparts. In previous studies targeting exclusively elderly breast cancer patients, primary hormonotherapy without further excision of operable tumors, breast conserving surgery without adjuvant radiotherapy to whole breast and, as well as ommision of axillary surgery in clinically node negative patients were questioned, seperately. In this comprehensive review, all available evidences regarding surgical treatment of breast cancer in elderly are provided in order to assess the rationality of these treatment diversions. As a conclusion, before implementing these less aggresive treatment modalities in physiologically fit elderly, results of studies with high power and longer follow-up should be awaited. Therefore, omission of standart treatment modalities should be regarded only for frail elderly with decreased life expectancy.
Keywords: Breast cancer; Elderly; Primary hormonotherapy; Surgery